A voyage of discovery towards the North Pole : performed in His Majesty's ships Dorothea and Trent, under the command of Captain David Buchan, R.N., 1818 : to which is added, a summary of all the early attempts to reach the Pacific by way of the Pole - Beechey, Frederick William (Richard Bentley Publisher in Ordinary to Her Majesty, 1843)
by Captain F.W. Beechey Handschriftliches Exlibris: "Edward E. [.] Oct. 1909" 011288529_0001 Exemplar der ETH-BIB